Influnce of Dietary Soy Acid Oil on Growth Performance, Carcass Characteristics and Chemical Composition of Muscles in Broiler Chicken - Dubey, Meenu; Tiwari, S.P.; Tiwari, R.P.; Khune, V.N.; Doneria, Raina (Indian Journal of Animal Nutrition, 2018)
Day old Vencobb broiler chicks (n= 360) were randomly divided into 6 treatment groups with 4 replicates of 15 chicks in each. Group T1 served as control while treatments T2, T3, T4, T5 and T6 contained 1, 1.5, 2, 2.5 and 3% of soy acid oil (SAO) in the diet, respectively. The body weight at 6 week of age was higher (P<0.05) in birds fed diet with high levels (2.5 and 3%) of soy acid oil. Feed intake was higher (P<0.05) in groups T5 and T6 as compared to other groups. The overall feed efficiency at 6 week was better (P<0.05) in group T5 as compared to T2, however, the variation among other groups was non-significant. The eviscerated weight was more (P<0.05) in birds fed diet with 2 and 3% SAO. Dressed weight was also higher (P<0.05) in birds fed diet with 3% SAO. There was significant (P<0.05) increase in back and neck yield while thigh yield decreased (P<0.05) in birds fed diets with SAO above 1.5% level. The relative weight of thymus improved due to inclusion of SAO irrespective of levels. There was increase (P<0.05) in the relative weight of bursa in treatment T6 as compared to control. The level of SAO did not influence the DM, protein and total lipid content of thigh and breast muscles. It was concluded that soy acid oil could be incorporated in broiler diet at 2.5% level as an alternative energy source as it improved growth performance, dressing percentage and immune status of broilers and did not have any adverse effect on the chemical composition of muscles.